Bioengineering the Bone Marrow Vascular Niche - Bessy, Thomas; Itkin, Tomer; Passaro, Diana (Frontiers in Cell and Developmental Biology, 2021)
The bone marrow (BM) tissue is the main physiological site for adult hematopoiesis. In recent years, the cellular and matrix components composing the BM have been defined with unprecedent high resolution, both at the molecular and structural levels. With the expansion of this knowledge, the possibility of reproducing a BM-like structure, to ectopically support and study hematopoiesis, becomes a reality. A number of experimental systems have been implemented and have displayed the feasibility of bioengineering BM tissues, supported by cells of mesenchymal origin. Despite being known as an abundant component of the BM, the vasculature has been largely disregarded for its role in regulating tissue formation, organization and determination. Recent reports have highlighted the crucial role for vascular endothelial cells in shaping tissue development and supporting steady state, emergency and malignant hematopoiesis, both pre- and postnatally. Herein, we review the field of BM-tissue bioengineering with a particular focus on vascular system implementation and integration, starting from describing a variety of applicable in vitro models, ending up with in vivo preclinical models. Additionally, we highlight the challenges of the field and discuss the clinical perspectives in terms of adoptive transfer of vascularized BM-niche grafts in patients to support recovering hematopoiesis.